PENERAPAN ARSITEKTUR TROPIS PADA PERANCANGAN KAWASAN WISATA PERIKANAN AIR TAWAR DI PARIGI, SULAWESI TENGAH - I Made Joshua Pratama; Anggraeni Dyah Sulistiowati; Harfa Iskandaria (MAESTRO, 2021)
Tourism is one of attractions in Indonesia and the biggest economic driver for the country. In order to drive the tourism in Indonesia for the better, its development needs to reach the area of multidisciplinary sector, such as inland public water fishery sector. In terms of potency, land availability and the source of inland fishing are huge. So therefore, with the design of freshwater fishery tourism area it is hoped to accommodate tourism management and the development of inland public water fishery sector especially in the region Parigi, Central Sulawesi. The tourism applies the concept of tropical architecture, which adapts to the regional climatic condition of Parigi so it can support the building function and convenience for users.